My Fault? Coworker Incivility and Organizational Citizenship Behavior: The Moderating Role of Attribution Orientation on State Guilt - Wang, Qiong; Teng, Xiaofei; Cai, Zijun; Qu, Yi; Qian, Jing (Frontiers in Psychology, 2021)
The effect of workplace incivility on the behavior of individuals has been a widespread concern in recent years. Previous studies have largely linked uncivilized workplaces to discrete emotions such as anger and frustration, as well as negative behaviors such as withdrawal and aggression. However, few studies have focused on the specific role of introverted discrete emotions (i.e., guilt). At the same time, the role of individual differences (i.e., attribution orientation) has not been paid enough attention. Based on the attribution theory, this study examines how coworker incivility influences the organizational citizenship behavior (OCB) of individuals and the moderating role of internal attribution orientation on this process. Using the data of 109 employees for 10 consecutive working days as samples, we employed the PROCESS macro and MPLUS to examine our hypotheses. The results indicated that coworker incivility experience was positively related to the state guilt of employees only when they were high in internal attribution orientation rather than low. State guilt, in turn, was positively related to their OCB. This study expands the research of emotional response to uncivilized experience and provides a new perspective to understand the relationship between workplace incivility and potential positive outcomes. The implications of the general findings are discussed.